Coagulopathy in the experimental rats elicited by Vipera berus berus or Vipera berus nikolskii envenomation - Tetiana Halenova, Nataliia Raksha, Oleksandra Kostiuk, Tetiana Andriichuk, Liudmyla Ahafonova, Kostiantyn Ahafonov, Viktoriia Piliponova, Oleksandr Maievskyi, Olexii Savchuk (Journal of Applied Pharmaceutical Science, 2025)
Viper snakebite is considered to be a serious and life-threatening medical problem due to its ability to cause various types of coagulopathies. The current study aimed to investigate the effects of Vipera berus berus and Vipera berus nikolskii venoms on hemostasis in rats. To determine the possible mechanisms of coagulopathy that occurred as a post-bite complication, various hemostatic parameters were studied in experimental animals 24 hours after a single intraperitoneal injection of V. b. berus or V. b. nikolskii venom. The obtained results were compared to those of the control group, composed of the rats not-treated with viper venom. Our results revealed the state of hypocoagulability in both groups of envenomed rats, which was accompanied by prolongation of plasma coagulation in the thrombin time test, reduction in plasma fibrinogen level, increased fibrin/fibrinogen degradation products, as well as functionally inactive prothrombin forms compared to the control. Both venoms also enhanced the heparin activity and inhibited the antithrombin III activity. Furthermore, severe alterations in fibrinolysis were noticed after venom injection. An increased level of plasmin activity was accompanied by a significant decrease in α-2-antiplasmin activity in the plasma of envenomed rats. It is concluded that V. b. berus and V. b. nikolskii venom toxins have significant effects on plasma coagulation and fibrinolysis and that viper snakebite could be an important risk factor for coagulopathy development.
Keywords: Snake venom, Vipera berus berus, Vipera berus nikolskii, coagulopathy, fibrinolysis, coagulation, thrombin time